Oropharyngeal candidiasis in children with lymphohematopoietic malignancies in Mashhad, Iran - Fariba Berenji; Nona Zabolinejad; Zahra Badiei; soraya Kakhi; Zohre Andalib Aliabadi; Majid Ganjbakhsh (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Over the past years, the role of fungi as a cause of nosocomial infections in hospitalized patients has been accentuated. Candida species constitute an important group of fungi causing diseases in immunocompromised patients. Oropharyngeal candidiasis continues to be a prevalent infection in immunodeficient patients. In this study, we aimed to determine the incidence of oropharyngeal candidiasis in children with lymphohematopoietic malignancies. Materials and Methods: In total, 102 patients with lymphohematopoietic malignancies and 50 healthy controls were examined in terms of Candida infections via direct sampling of the oropharyngeal cavity. Fresh smears were prepared with 10% potassium hydroxide and Gram staining was carried out. Subsequently, the obtained specimens were cultured on Sabouraud dextrose agar for further analysis. Results: The most common Candida species were Candida albicans (31%), other non-C. albicans species (14.7%), C. glabrata (6.8%), and C. krusei (0.98%) in the case group, while in the control group, other non-C. albicans species (10%) and C. albicans (8%) were the most common species. Conclusion: In the present study, Candida species were the most common fungal pathogens in pediatric cancer patients; therefore, efforts should be made to prevent fungemia and fungal pneumonia. Also, non-C. albicans species must be considered as a new risk factor for pediatric cancer patients.